Insights into the pathogenesis of cystoid macular edema: leukostasis and related cytokines - Yoo-Ri Chung (International Journal of Ophthalmology, 2019)
Cystoid macular edema (CME) is the abnormal collection of intraretinal fluid in the macular region, especially in the inner nuclear and outer plexiform layers. CME leads to severe visual impairment in patients with various retinal diseases, such as diabetic retinopathy, retinal vascular occlusion, choroidal neovascularization, and uveitis. Although various retinal conditions lead to CME, a shared pathogenesis of CME is involved in these diseases. Accordingly, the pathogenesis of CME based on vasogenic mechanisms is first discussed in this review, including vascular hyperpermeability, leukostasis, and inflammation. We then describe cytotoxic mechanisms based on retinal Müller cell dysfunction. This comprehensive review will provide an understanding of the pathogenesis of CME for potential therapeutic strategies.